Forest strips left along water and bog can be valuable for birds. A case of experimental cutting - Hågvar, Sigmund; Bækken, Bjørn Tore (Ornis Norvegica, 2005)
An experimental cutting was performed in Grue municipality, Hedmark, to study the value for birds of retaining a forest strip along bog and water. Two study areas of mature coniferous forest were selected, each 600 x 200 m, with one of the long sides towards either water or bog. Before logging started, all bird territories were mapped during two years. In the third breeding season, a 50 m wide forest strip remained adjacent to water and bog, and in the fourth season a 25 m wide forest strip. Both along bog and water, the 25 m wide forest strip supported a species- and individual-rich bird fauna, with higher density than before cutting. This is in accordance with an extensive study in remaining forest strips adjacent to water and bogs in South-East Norway, where the authors adviced to set aside 30 m wide strips. Literature data indicate that the rich bird life in such buffer zones may be due to a concentration of insects blown in from the open clearcut area.